2020
DOI: 10.12706/itea.2020.006
|View full text |Cite
|
Sign up to set email alerts
|

Nuevos indicadores de carnes DFD: estrés oxidativo, autofagia y apoptosis

Abstract: En el ganado vacuno, el estrés pre-sacrificio provoca la aparición de carnes conocidas como DFD (Dark, Firm, Dry), que se identifican por un descenso anómalo del pH muscular post-mortem y que muestran serios problemas de calidad, lo cual disminuye su valor comercial. El objetivo de este trabajo es conocer las diferencias en los procesos de estrés oxidativo, en los mecanismos de supervivencia/muerte celular (autofagia/apoptosis) y en biomarcadores proteómicos a las 24 h post-mortem, entre canales que mostraron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
(62 reference statements)
0
9
0
1
Order By: Relevance
“…Proteomic studies have reported the differential expression of Hsp70 in meat with variable quality traits [ 22 , 38 ]. Several studies have correlated meat quality with Hsp70 under stress situations [ 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Proteomic studies have reported the differential expression of Hsp70 in meat with variable quality traits [ 22 , 38 ]. Several studies have correlated meat quality with Hsp70 under stress situations [ 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, band M24 was identified as FHL1 and, contrary to what was found for FHL2, only a significant decrease with post-mortem ageing and a significant interaction F × TL (E-NM > E-M = I-M > I-NM) was observed ( p < 0.001). Previous studies found increased intensity of FHL1 in DFD meat [ 16 , 22 , 57 ].…”
Section: Resultsmentioning
confidence: 87%
“…On the other hand, animal handling may affect animal’s emotional state, hence inducing pre-slaughter stress (PSS), whose influence on the post-mortem process of muscle-to-meat conversion has been shown in pigs [ 13 , 14 ] and in cattle [ 3 , 9 , 10 , 15 , 16 , 17 , 18 ]. Those biochemical changes were evidenced using several high-throughput OMICs methods, including proteomics that revealed, for instance, that the meat tenderizing process involves myriad pathways, such as the degradation of structural proteins, energy metabolism pathways, response to stress, apoptosis, autophagy, and signaling pathways [ 19 , 20 ] as confirmed recently by the integromics meta-analysis study of Gagaoua et al [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have described the effect of handling practices on meat characteristics 24,32,33 and some of them have reported differences on caspase 3 expression patterns between normal and DFD samples, finding higher caspase 3 regulation levels in DFD samples at 24 h post mortem. 14,15 However, no studies have been previously reported concerning the relationship between caspase activity and stress-related factors. From our study we hypothesized that, depending on the external stimulus affecting animals before slaughter, different caspase activation responses could be triggered.…”
Section: Resultsmentioning
confidence: 99%
“…13 In this line, some authors found a higher expression of the caspase 3 large subunit in DFD beef samples at 24 h post mortem times. 14 In the present study, and for the first time, the study of apoptosis as a way to understand the influence of pre-slaughter handling practices on biochemical muscle characteristics of several bovine breeds is proposed. The research investigated the activity of executioner caspases 3/7 and initiator caspase 9 over time (2, 8, and 24 h post mortem) in loin samples of three Spanish beef cattle breeds managed under different feeding systems (intensive versus semi-extensive) and transport/lairage (mixed versus nonmixed with unfamiliar animals) conditions.…”
Section: Introductionmentioning
confidence: 99%